1973
DOI: 10.1029/jb078i029p06863
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence of Hawaiian basalts

Abstract: The thermoluminescence (TL) of eight Hawaiian basalt flows, ranging in age from 12 to 17,360 years, was studied to test the feasibility of TL as a dating technique. Plagioclase from tholeiitic basalt has a single glow peak at 300°C, and TL peak heights, when they are normalized for susceptibility to radiation and for annual dose from U, Th, and K contained in the rock, show a good linear correlation with the known ages of the flows. The results from two alkalic basalts do not correlate so well with known age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Thermoluminescence (TL) has been recognized for some time as having potential for use in dating these types of rocks, and several attempts have been made to obtain absolute TL ages for young lavas of a wide range of compositions using techniques developed for archeologic artifacts, but most have been relatively unsuccessful [Sabels, 1963;Aitken et al, 1968;Hwang, 1970;Aitken and Fleming, 1971]. One of the most recent and encouraging studies of the TL properties of volcanic rocks was that by Berry [1973], who identified a progressive increase in the magnitude of the natural to artificial TL ratio with age for several dated Hawaiian tholeiitic basalts. Unfortunately, these data, too, proved to be unsuitable for the direct calculation of absolute TL ages, but the predictable nature of the increase in the TL ratio with age was intriguing because it suggested a uniform process of TL accumulation in rocks of a restricted compositional range.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoluminescence (TL) has been recognized for some time as having potential for use in dating these types of rocks, and several attempts have been made to obtain absolute TL ages for young lavas of a wide range of compositions using techniques developed for archeologic artifacts, but most have been relatively unsuccessful [Sabels, 1963;Aitken et al, 1968;Hwang, 1970;Aitken and Fleming, 1971]. One of the most recent and encouraging studies of the TL properties of volcanic rocks was that by Berry [1973], who identified a progressive increase in the magnitude of the natural to artificial TL ratio with age for several dated Hawaiian tholeiitic basalts. Unfortunately, these data, too, proved to be unsuitable for the direct calculation of absolute TL ages, but the predictable nature of the increase in the TL ratio with age was intriguing because it suggested a uniform process of TL accumulation in rocks of a restricted compositional range.…”
Section: Introductionmentioning
confidence: 99%
“…Great improvements have been made recently in understanding the occurrences of charcoal beneath lava flows (Lockwood and Lipman, in 14 press), and many new C dates from Hawaii have resulted (Kelley and others, 1979;Kelley, 1979 Thermoluminescence dating has shown some promise (Berry, 1973), but attempts to use it on very young tholeiitic flows like those on the surface of Kileaua have been unsuccessful (R. J. May, 1979).…”
Section: Chronologymentioning
confidence: 99%
“…A preliminary investigation by Berry (1973) of the TL properties of plagioclase separates from a suite of six samples of tholeiitic and alkalic basalt from the island of Hawaii ranging in age from approximately 225 to 17,000 years led to the identification of a progressive increase in the TL of the samples with increasing age. No attempt was made on the basis of the preliminary results to develop a dating method for these rocks, but the data display the same basic TL relative to age relation identified by other workers for prehistoric pottery.…”
Section: Previous Workmentioning
confidence: 99%
“…The investigation by Berry (1973) prompted May to initiate a more detailed and comprehensive study of the potential of using TL to date Hawaiian basalts. The principal impetus for the research was the possibility of using TL dating to bridge the significant age gap that exists between the limits of the two principal methods for dating young rocks, radiocarbon and potassium-argon.…”
Section: Purpose and Goalsmentioning
confidence: 99%